2017
DOI: 10.15201/hungeobull.65.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Geographical characteristics of contemporary international migration in and into Europe

Abstract: The study offers a short geographical overview of migration studies and theories, doing so in the context of the European migration crisis of [2015][2016]. It outlines the history of international migrations affecting Europe (immigration, emigration, migration within Europe and between countries) and the demographic effects of such migration on the present European population. It then analyses and examines the global and regional causes of recent migration to Europe (the European Economic Area, EEA), the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
4
0
4
Order By: Relevance
“…Since the 1980s, the scientific research on return has become increasingly significant in migration studies (Glaser-Habers 1974, Gmelch 1980, Cassarino 2004, van Houte-Davids 2008, de Haas 2010, Nadler et al 2016. To date, the primary concern of Hungarian social geography has mainly focused on emigration in terms of several different migration processes, such as migration of refugees to Europe (Kocsis et al 2016, Farkas-Dövényi 2018. Studies on return migration, its individual and social aspects, and the practical, economic-development utilisation of this phenomenon (Kovács et al 2013, Lados-Hegedűs 2016, Csányi 2018) are even rarer.…”
Section: The Definition Of Return Migration and Its Theoretical Appromentioning
confidence: 99%
“…Since the 1980s, the scientific research on return has become increasingly significant in migration studies (Glaser-Habers 1974, Gmelch 1980, Cassarino 2004, van Houte-Davids 2008, de Haas 2010, Nadler et al 2016. To date, the primary concern of Hungarian social geography has mainly focused on emigration in terms of several different migration processes, such as migration of refugees to Europe (Kocsis et al 2016, Farkas-Dövényi 2018. Studies on return migration, its individual and social aspects, and the practical, economic-development utilisation of this phenomenon (Kovács et al 2013, Lados-Hegedűs 2016, Csányi 2018) are even rarer.…”
Section: The Definition Of Return Migration and Its Theoretical Appromentioning
confidence: 99%
“…In Central and Eastern Europe immigration did not cause problems that would have affected the everyday lives of people until very recently (Kocsis, K. et al 2016). Several researchers confirmed that until 2015 the citizens of Hungary did not consider immigration particularly dangerous.…”
Section: The Migration Crisis and The Importance Of Bordersmentioning
confidence: 99%
“…However, as a result of the migration crisis that has been centred since 2015 (Kocsis et al 2016), an anti-immigrant radicalism has begun that was only experienced in Western Europe previously. This topic was completely taken away by the mainstream right-wing Fidesz from the radical, but moderating Jobbik, thus the claims of Michael Minkenberg realised that proves the mainstream right-wing party have radicalised to curb the radical right-wing party (Minkenberg 2015).…”
Section: Detecting the Indicators Of National Radicalisationmentioning
confidence: 99%